Genre Analysis of Memo from Headmaster to Teachers - Ghazi Mohammad Takal; Mujtaba Jamal; Abdul Rahmat (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
Discourse analysis has always been a great tool for analyzing both spoken and written discourses in various discourse communities. Specifically, it has largely been used for written discourse analysis. For instance, it has been used in analysis of memos. Memos have been a valuable part of written discourse in different settings. Thus, this paper is the analysis of a memo written by a school headmaster. The author used Genre Analysis as a discourse analysis for analyzing the memo text in this paper. Although there are several models for genre analysis, Genre Analysis of Vijay. K Bhatia Model has been used in this study. The findings revealed that the memo was related to a professional genre of school while meeting not the entire characteristics of professional genre. The research suggested that future studies be conducted concerning memo analysis.